The Big Picture: Effects of Surround on Immersion and Size Perception. (October 2014) - Baranowski, Andreas M; Hecht, Heiko
Despite the fear of the entertainment industry that illegal downloads of films might ruin their business, going to the movies continues to be a popular leisure activity. One reason why people prefer to watch movies in cinemas may be the surround of the movie screen or its physically huge size. To disentangle the factors that might contribute to the size impression, we tested several measures of subjective size and immersion in different viewing environments. For this purpose we built a model cinema that provided visual angle information comparable with that of a real cinema. Subjects watched identical movie clips in a real cinema, a model cinema, and on a display monitor in isolation. Whereas the isolated display monitor was inferior, the addition of a contextual model improved the viewing immersion to the extent that it was comparable with the movie theater experience, provided the viewing angle remained the same. In a further study we built an identical but even smaller model cinema to unconfound visual angle and viewing distance. Both model cinemas produced similar results. There was a trend for the larger screen to be more immersive; however, viewing angle did not play a role in how the movie was evaluated.